2010
DOI: 10.1007/s00404-010-1611-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with recurrence of cervical intraepithelial neoplasia after conization in HIV-infected and noninfected women

Abstract: Human immunodeficiency virus infection and glandular involvement are associated with CIN recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
2
27
1
Order By: Relevance
“…The recurrent rate of CIN treated with LEEP in the present study was 2.8%; this rate was substantially lower when compared with the rates of 5-24% in previous reports (Alvarez et al, 1994;Ayhan et al, 2009;Lodi et al, 2011). The glandular involvement and positive margins in the LEEP specimen were potential factors for disease recurrence (Kietpeerakool et al, 2007;Lodi et al, 2011;Kir et al, 2012).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The recurrent rate of CIN treated with LEEP in the present study was 2.8%; this rate was substantially lower when compared with the rates of 5-24% in previous reports (Alvarez et al, 1994;Ayhan et al, 2009;Lodi et al, 2011). The glandular involvement and positive margins in the LEEP specimen were potential factors for disease recurrence (Kietpeerakool et al, 2007;Lodi et al, 2011;Kir et al, 2012).…”
Section: Discussioncontrasting
confidence: 51%
“…The glandular involvement and positive margins in the LEEP specimen were potential factors for disease recurrence (Kietpeerakool et al, 2007;Lodi et al, 2011;Kir et al, 2012). Nevertheless, the present study found that only positive margin status had a marginally significant correlation with the recurrence (p=0.05).…”
Section: Discussionmentioning
confidence: 99%
“…lesion size) explain these differences? A recent systematic review, and subsequent publications, suggest that HIV‐infected women are more likely to have treatment failures/recurrent disease, but the evidence for each treatment modality is very limited. The most likely explanation is that HIV‐infected women have larger lesions due to immune suppression and therefore the lesion margins are not clear, leading to failure/recurrence. Does the healed epithelium following ablation allow for effective monitoring and diagnosis of recurrent (untreated) disease?…”
Section: Future Research On Treatment Methodsmentioning
confidence: 99%
“…However, the goal of this visualization is only to determine what treatment/management is needed-that is, whether there are con- explain these differences? A recent systematic review, 30 and subsequent publications, 28,[31][32][33] suggest that HIV-infected women are more likely to have treatment failures/recurrent disease, but the evidence for each treatment modality is very limited. The most likely explanation is that HIV-infected women have larger lesions due to immune suppression 28 and therefore the lesion margins are not clear, 32 leading to failure/recurrence.…”
Section: Visualizing Lesions For Ablative Treatmentmentioning
confidence: 99%
“…7,8 HIV-infected women also have increased rates of recurrence after treatment for cervical intraepithelial neoplasia 2+ (CIN2+), the immediate cervical cancer precursor. 9,10 Although access to highly active antiretroviral therapy (HAART) in many countries has dramatically increased over the past decade, the impact of HAART on the development of cervical precancer and recurrence after treatment remain unclear. 1115 This means that an increasing number of HIV-infected women are living longer with a potentially higher risk for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%